Comparing the succession of microbial communities throughout development in field and laboratory nests of the ambrosia beetle Xyleborinus saxesenii - Diehl, Janina M. C.; Keller, Alexander; Biedermann, Peter H. W. (Frontiers in Microbiology, 2023)
Some fungus-farming ambrosia beetles rely on multiple nutritional cultivars (Ascomycota: Ophiostomatales and/or yeasts) that seem to change in relative abundance over time. The succession of these fungi could benefit beetle hosts by optimal consumption of the substrate and extended longevity of the nest. However, abundances of fungal cultivars and other symbionts are poorly known and their culture-independent quantification over development has been studied in only a single species. Here, for the first time, we compared the diversity and succession of both fungal and bacterial communities of fungus gardens in the fruit-tree pinhole borer, Xyleborinus saxesenii, from field and laboratory nests over time. By amplicon sequencing of probed fungus gardens of both nest types at three development phases we showed an extreme reduction of diversity in both bacterial and fungal symbionts in laboratory nests. Furthermore, we observed a general transition from nutritional to non-beneficial fungal symbionts during beetle development. While one known nutritional mutualist, Raffaelea canadensis, was occurring more or less stable over time, the second mutualist R. sulphurea was dominating young nests and decreased in abundance at the expense of other secondary fungi. The quicker the succession proceeded, the slower offspring beetles developed, suggesting a negative role of these secondary symbionts. Finally, we found signs of transgenerational costs of late dispersal for daughters, possibly as early dispersers transmitted and started their own nests with less of the non-beneficial taxa. Future studies should focus on the functional roles of the few bacterial taxa that were present in both field and laboratory nests.